Geospatial Distribution of Landslides in the Lumbini Province - Subedi, Raksha; Gyawali, Pratik; Chaudhary, Prashant (Journal of Nepal Geological Society, 2025)
Lumbini Province, located in western Nepal, is known for its diverse geography, ranging from the low land Tera to the rugged hills of the Chure and Mahabharat ranges. The Main Boundary Thrust passes through the region, which makes the geology more complicated due to tectonic movements. This study aims to analyze the geospatial distribution of Landslides in Lumbini province as well as the causes and triggering factors in different areas in the province. First, a preliminary literature review is done on Landslides and its possible triggering factors. The data for this project are retrieved from the Bipad Portal (2012-2024), rainfall records from DHM, seismic and geological maps from the Department of Mines and Geology, and road infrastructure details from the Department of Roads. The data is analyzed by statistical methods to understand the triggering factors (rainfall, tectonic activity, toe-cutting, and road construction) and how these factors influence landslides over the years from 2012-2024. The study shows that the area most affected by landslides are Rolpa and Eastern Bulum, which are located in the region influenced by the tectonic activity along the MBT. The meteorological station in Baldyanggadi, Palpa, also showed a significant increase in rainfall from 90.4mm to 252.0mm on September 28, 2024, which resulted in several landslides. The weak Geology of Chure helps in triggering Landslides as major cities are located in and around Chure in this province with a larger population density, rather a small size of the landslide could be huge in terms of inventory value. Important infrastructures and historical and ecological complex ecosystems in this region can be harmed by landslides in the future. Therefore, the findings suggest that small technical and financial steps in the field can reduce the risk of Landslides in the Lumbini province by a high percentage.